Deterioration of the environment and undefined type of structuring: Eastern Mediterranean coasts of Anatolia-Goksu Delta - Erkan, N.; Hamamcioglu, C. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2009)
The Eastern Mediterranean coasts of Anatolia are situated on the south of East Taurus Mountains and provide natural and cultural assets distinguished by the Mediterranean Sea. Fertile coastal plain, citrus fruit gardens, adequate climate, long beaches, rivers, deltas, forests, specific flora and fauna constitute the reserves of the area. However, in the last decade, Eastern Mediterranean coasts of Anatolia have started to be influenced by a kind of an inhuman and 'undefined type of structuring' which expands disjointedly into the existing settlements. Influenced by domestic tourism and some industrial activities, the scale of such activities can be devastating. Furthermore, these uses often occur along coasts and over the fertile coastal agricultural lands and threaten and to encroach upon the Goksu Delta which is under the protection of an international treaty and national policies. The objective of this paper is to explore the concept of water as a structuring element of urbanity in the Eastern Mediterranean coasts of Anatolia in the context of ecological and management regulations. This research was carried out in the 2006-2007 academic year in the context of planning education of the Department of Urban and Regional Planning of Yildiz Technical University.
Keywords: Eastern Mediterranean coasts of Anatolia; natural environment; unrestrained structuring; water as a structuring element; Engineering